Thirty-First Annual Homecoming, Pope's Chapel United Methodist Church, October 4, 1987 - (:unkn) unknown (Pope's Chapel First Methodist Church, 1987)
Thirty-First Annual Homecoming, Pope's Chapel United Methodist Church, October 4, 1987. John Pike, pastor. Event program. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_19871004.pdf. 4 pages. 20481603 bytes (master).
Keywords: Methodists; Methodist church; Homecoming; Programs (Publications); Wilkes County (Ga.); Pope's Chapel United Methodist Church (Wilkes County, Ga.); Asbury, Francis; Bamford, Sophia; Bohler, Eugenia; Boyd, David; Boyd, James W.; Boyd, John W.; Brian, Brantly Vee; Bufford, Ethell; Bufford, Pearl R.; Cantrell, Jim; Cash, M. T.; Chafin, David; Chafin, Elizabeth; Chafin, Malcolm; Combs, Farmer; Combs, Hazel; Fortson, Benjamin W.; Fortson, Benjamin Winn; Grimes, Steve; Harris, Lundye; Humphries, Thomas; Landrum, John; McIntosh, Aaron; Neal, Augustus A.; Ogilvie, Hannah Rebecca; Oglesby, Evelyn; Pike, John; Pike, Sally; Pope, Henry; Pullen, Thomas; Sale, David; Spence, John; Wheatley, Elaine; Wheelis, C. V.; Wheelis, C. V.; Wiggins, Tom; Wolfe, Janelle Sale; Young, Charles